Adhesive properties of thiol-acrylate-epoxy composites obtained by dual-curing procedures. (January 2022) - Russo, Claudio; Bustamante, Francesc; Fernández-Francos, Xavier; De la Flor, Silvia
Abstract: Composite materials were prepared using a thiol-acrylate-epoxy dual-curing system filled with Boron Nitride (BN) agglomerates. The adhesive properties obtained with two different acrylate ratios (ra ) were tested to characterize differences and applicability of final thermosets. The effect of bondline thickness, BN wt% and curing procedure on the adhesive strength was evaluated for both acrylate ratios r a by means of lap-shear tests. Materials with viscous intermediate (ra  = 0.2) results were observed to have the best performance reaching a maximum of almost 5 kN with 20 wt% of BN. On the other hand, materials with an intermediate gelled network (ra  = 0.5) showed a high accuracy in dimension control but lower values of adhesive strength were obtained. A decrease of adhesive strength with the increase of thickness was found for both ra, while the increase of BN wt% lead to higher adhesive strength. The beneficial effect of dual-curing processing on the adhesive properties of liquid intermediate materials was also experimentally demonstrated.